Evaluation of body composition with bioimpedence. A comparison between athletic and non-athletic children. Issue 6 (3rd July 2017) - Meleleo, Domenico; Bartolomeo, Nicola; Cassano, Liliana; Nitti, Alessandro; Susca, Giovanna; Mastrototaro, Giuseppina; Armenise, Umberto; Zito, Annapaola; Devito, Fiorella; Scicchitano, Pietro; Ciccone, Marco Matteo
Abstract: Purpose: Conventional Bioelectrical Impedance Analysis (BIA) or Bioelectrical Impedance Vector Analysis (BIVA) can provide direct evaluations of body composition. The purpose of this study was to evaluate lean and fat mass (FM), and hydration of children involved in daily competitive sports. Methods: 190 non-athletic [8.2–10.5 years] and 29 competitive children [8.0–10.5 years] were enrolled. They were evaluated: at baseline ( t0 ), 6 months ( t1 ) and one year ( t2 ). Anthropometric, BIA and BIVA, lean and FM, and hydration evaluations were performed. Results: Resistance (R/h) and reactance (Xc/h) were lower at t 0 in competitive individuals when compared to controls. Xc/h (+3.28) significantly increases in competitive when compared to non-competitive individuals (+0.66, p for difference: 0.011), while phase angle (PA) was lower at t 0 (5.72 vs. 6.17, p < .001) and after 6 months ( p = .001). Total body water adjusted for height (TBW/h) significantly increased only in non-athletes (+0.50 ± 0.13, p < .001) between t0 and t1 . At t1, extracellular water (ECW) significantly decreased ( p = .026) in the two groups: −0.45 ± 0.19% in non-competitive, −1.63 ± 0.49% in competitive subjects, while intracellular water (ICW) increased. At one-year follow-up ( t2 ), there were no statistically significant differences in R/h, Xc/h and PA in competitive individuals when compared to baseline and t1 . Furthermore, we observed at t2 that hours/week of training, age, male gender and body mass index can influence FFM/h and FM/h in both competitive and non-competitive subjects. In particular, a direct correlation was for hours/week and FFM/h, inverse for hours/week and FM/h. Conclusions: Body mass index does not allow evaluating differences in lean body mass and FM between athletes and non-athletes. BIA and BIVA can give more reliable details about body composition differences in competitive adolescents and non-competitive, outlining a progressive decline in ECW and increase in ICW without affecting TBW composition of athletes.